2005
DOI: 10.2527/2005.83102440x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dried full-fat corn germ and vitamin E on growth performance and carcass characteristics of finishing cattle1

Abstract: Two experiments were conducted to evaluate dried full-fat corn germ (GERM) as a supplemental fat source in cattle finishing diets. In Exp. 1, 24 pens totaling 358 crossbred beef steers with an initial BW of 319 kg were allowed ad libitum access to diets containing dry-rolled corn, 35% wet corn gluten feed, and 0, 5, 10, or 15% GERM on a DM basis. Increasing GERM decreased (linear; P < 0.02) DMI and increased (quadratic; P < 0.02) ADG. Steers fed 10% GERM had the greatest ADG (quadratic; P < 0.02) and G:F (quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…This protection may occur if the oil is still in the intact germ portion of the kernel and, therefore, not inhibitory to microbes. However, Montgomery et al (2005) did not observe a difference between cattle fed full-fat germ from corn or tallow with diets containing 4% supplemental fat.…”
Section: Methodsmentioning
confidence: 64%
“…This protection may occur if the oil is still in the intact germ portion of the kernel and, therefore, not inhibitory to microbes. However, Montgomery et al (2005) did not observe a difference between cattle fed full-fat germ from corn or tallow with diets containing 4% supplemental fat.…”
Section: Methodsmentioning
confidence: 64%
“…In a review about the effects of vitamin E on performance of feedlot cattle, Secrist et al (1997) found that indicators of fat deposition (fat thickness, marbling score and yield grade) tended to increase with vitamin E supplementation, but that was not observed in this study. Generally, vitamin E supplementation (vitamin E levels 224 to 1200 IU/animal per day) has not been found previously to affect carcass characteristics or quality and yield grades of beef cattle (Realini et al, 2004;Montgomery et al, 2005;Lee et al, 2008). Effects of vitamin E supplementation depend on its level, previous Nassu, Dugan, Juá rez, Basarab, Baron and Aalhus nutritional history, vitamin E status of the cattle at the start, stress level of animals and vitamin E content of the basal diet, as well as genetics, which is related to the ability of individual animals to tolerate handling and feedlot conditions (Secrist et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of vitamin E supplementation of feedlot cattle on growth performance has not been consistent. Numerous studies (Arnold et al 1992;Zinn et al 1996;Rivera et al 2002;Carter et al 2005;Montgomery et al 2005) have failed to show a growth performance response to supplemental vitamin E. In other instances, vitamin E supplementation enhanced daily body weight (BW) gain (Reddy et al 1987;Pehrson et al 1991;Burken et al 2012). Inconsistencies in growth performance responses may be attributable to previous nutritional status, including vitamin E status, dietary vitamin E intake, and animal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies in growth performance responses may be attributable to previous nutritional status, including vitamin E status, dietary vitamin E intake, and animal stress. Apart from growth performance affects, per se, vitamin E supplementation may enhance immunocompetence (Rivera et al 2002) and carcass characteristics (Rivera et al 2002;Montgomery et al 2005) or meat quality as related to colour stability (Arnold et al 1992(Arnold et al , 1993.…”
Section: Introductionmentioning
confidence: 99%